Identification key for Pliocene and Quaternary Spiniferites taxa bearing intergonal processes based on observations from estuarine and coastal environments. (20th December 2018) - Limoges, Audrey; Londeix, Laurent; Mertens, Kenneth Neil; Rochon, André; Pospelova, Vera; Cuéllar, Tomasa; de Vernal, Anne
Abstract: The use of dinoflagellate cyst assemblages as a tool for palaeo-environmental reconstructions strongly relies on the robustness of cyst identification and existing information on the distribution of the different species. To this purpose, we propose a functional key for the identification of Pliocene and Quaternary Spiniferites bearing intergonal processes and depict the range of morphological variation of the different species on the basis of new observations from estuarine and coastal regions. Accordingly, the description of Spiniferites mirabilis is emended to include the new subspecies Spiniferites mirabilis subsp. serratus . We also report the occasional presence of intergonal processes in Spiniferites bentorii and Spiniferites belerius . This key aims to facilitate identification of this group of Spiniferites bearing intergonal processes and standardize cyst identification among researchers.